Anorexia nervosa: Trapped between Mind and Body: An Analysis of Causes, Symptoms, and a Holistic Approach to Therapy - Muciek, Adrianna; Mocarska, Martyna; Mencel, Jan; Strakowska, Katarzyna; Opalska, Laura; Maryńczak, Anna; Nitschke, Nicole; Orłowska, Anna (Quality in Sport, 2025)
Anorexia nervosa is a serious eating disorder marked by an intense fear of gaining weight and a distorted body image, leading to extreme food restriction and dangerous weight loss. It most commonly affects adolescents and young adults, particularly women. The causes of anorexia are complex, involving a combination of genetic, psychological, and socio-cultural factors. Key symptoms include significant weight loss, obsessive thoughts about food, and excessive physical activity. Effective treatment requires a multidisciplinary approach, integrating medical stabilization, nutritional support, psychotherapy, and, when necessary, pharmacotherapy. Long-term care and relapse prevention are essential for sustained recovery. Raising public awareness and promoting healthy body image is vital in preventing anorexia and its complications. This article explores the causes, symptoms, and treatment options for anorexia nervosa, highlighting the importance of early intervention in improving outcomes.